On composite length-biased exponential-Pareto distribution: Properties, simulation, and application in actuarial science - Benchettah, Moulouk Halima; Zeghdoudi, Halim; Raman, Vinoth (Frontiers in Applied Mathematics and Statistics, 2023)
The compositelength-biased exponential Pareto (CLBEP) distribution is a new composite distribution that is introduced in this paper. This model’s probability density function, moments, and quantiles, among other statistical characteristics, are determined mathematically. The parameters’maximum likelihood estimation and stochastic ordering are discussed. A comparison study with other new composite and conventional distributions is also included. Specifically, using two actual fire insurance data sets, the goodness of fit of this new model is contrasted with the composite exponential-Pareto, composite lognormal-Pareto, and composite Rayleigh-Pareto distributions (Algerian and Danish …re insurance losses).